Rozwój kultury w mieście a wzory społeczno-kulturowe mieszkańców - Jacher, Władysław (Studia Etnologiczne i Antropologiczne, 2010)
The mechanism of functioning culture in a town demands cultural patterns within which cultural life is well ordered and available. Sociological research and observation refute the existing opinions — the stereotypes about culture in a town as if the numerous cultural devices available to its inhabitants would testify to the high development of culture. The existence of cultural integration in a town is very important as it means that there are alterna¬tives in the choice of cultural values and it is a higher stage in the development of culture. It assumes not only the accessibility and dissemination of culture but also to a higher and higher degree, the ability to choose cultural values which are the closest to a given man. The expression of cultural integration is the participation of town dwellers in culture which allows them to join actively not only to make use of culture but to create it at the same time. It should be noted that all fulfillment of potential abilities of the participation in culture is achieved in an individual act of expressing own interests and aspirations of town dwellers.